An investigation about origins: A brief history of the PCAOB'S regulatory model. Issue 2 (October 2018) - Sheu, Robert J.
Abstract: The scandals involving Enron, WorldCom, and Arthur Andersen are frequently cited as among the principal reasons for the passage of the Sarbanes–Oxley Act [Pub.L. 107–204, 116 Stat. 745, enacted July 30, 2002] (SOX) as well as the genesis of the Public Company Accounting Oversight Board (PCAOB). The PCAOB is a relatively new agency that was created to a play vital role as the regulator for auditors of U.S. public companies. For such an important organization, its background remains relatively unexamined. This paper seeks to extend the existing literature by examining the historical origins of the PCAOB and identifying the regulatory influences and prototypes of this regulatory agency. Was the organization's regulatory structure chosen arbitrarily? Were there various events as well as exemplar entities in the preceding decades that played an integral role in the eventual creation of the PCAOB? This research seeks to answer these questions.